The development of the reading comprehension—Progress monitoring (RC-PM) tool for late elementary students - Bogaert, Rielke; Merchie, Emmelien; Aesaert, Koen; Van Keer, Hilde (Frontiers in Education, 2023)
Notwithstanding reading comprehension is a key competence in today’s society, many late elementary students struggle with it. In this respect, effective instructional incentives are required to foster students’ reading comprehension. However, appropriate assessment instruments to monitor students’ reading comprehension on a regular basis and to make substantiated instructional decisions are lacking. Therefore, a Reading Comprehension – Progress Monitoring tool was developed, consisting of six parallel tests equivalent in difficulty and length. To this aim, classical test theory analyses, item response theory analyses, and automated test assembly were conducted (n = 3269 students). Suggestions for future research and practice are discussed.